Sustainable Governance and the Future of Islamic Boarding Schools: Strengthening Human Resources Based on Religious Values: Tata Kelola Berkelanjutan dan Masa Depan Pesantren: Penguatan Sumber Daya Manusia Berbasis Nilai-Nilai Keagamaan - Pramuja, Alvin Dian; Nurhafid Ishari; Zainul Arifin; Ahmad Hafidz Lubis (QULUBANA: Jurnal Manajemen Dakwah, 2024)
The objective of this study was to examine the Sustainable Governance in determining the Future of Pesantren using Various Strategies for Strengthening Human Resources at Mamba'ul Hikam Islamic Boarding School using qualitative and case study method. Data were collected through observation, interviews, and documentation. The results showed that Mambaul Hikam implemented a multifaceted strategy to improve the quality of human resources in religious beliefs. This strategy comprised various activities, such as congregational obligatory prayers, the performance of sunnah night prayers, which included Tahajjud and Witr, the observance of the Duha prayer, the conduction of 'istighosah' sessions every evening, as well as the recitation of the Tahlil and Burdah every Friday night. The recitation of the entire Qur’an (Khotmil Qur'an) took place every Friday, and was complemented by a 'madrasah diniah' (Islamic-focused subject) in the daytime. Students also attended formal school in the morning, the recitation of Surah Yasin before entering classes, followed by book study sessions after the Isya'. Furthermore, students actively participated in school activities such as 'PI' (Practice of Worship), which included book discussions and khutbah by room representatives on Tuesday nights, as well as direct advice from their mentors.